Return to work in patients with head and neck cancer: Systematic review and meta‐analysis. Issue 12 (19th September 2022) - Yu, Justin; Smith, Justin; Marwah, Ravi; Edkins, Oskar
Abstract: Background: The aim of this review was to determine the prevalence of return to work (RTW) amongst head and neck cancer (HNC) survivors and to determine its impact on quality of life (QoL). Methods: A literature search was conducted in PubMed, Scopus, Embase and CINAHL in March 2021. Articles were included if they reported the number of patients with HNC receiving definitive treatment who were working at the time of diagnosis and returned to work. Results: There were 21 articles deemed eligible for inclusion. Meta‐analysis suggested that 67% of patients with HNC who were employed at diagnosis RTW (95% CI 62%–73%, I 2 = 97.53%). Patients who RTW were demonstrated to have lower levels of anxiety and depressive symptoms on the Hospital Anxiety and Depression Scale. Conclusions: Return to work is an important clinical outcome which must be considered in the survivorship care of patients with HNC.